Serum cytokines and their predictive value in pulmonary involvement of systemic sclerosis - Becker, Mike Oliver; Radic, Mislav; Schmidt, Katrin; Huscher, Dörte; Arne, Riedlinger; Michelfelder, Marissa; Meisel, Christian; Ewert, Ralf; Burmester, Gerd Rüdiger; Riemekasten, Gabriela (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Objective: To identify serum cytokines which predict mortality and/or disease progression in patients with systemic sclerosis, especially with pulmonary involvement. Methods: Serum cytokines (IL-6, IL-7, IL-8, IL-10, CCL2, CCL4, TGF-β, TNF-α) were measured in 125 SSc patients, who were recruited and observed in our outpatient clinic. Of these, 60 had pulmonary involvement, classified as either interstitial lung disease (ILD, 43 patients), pulmonary arterial hypertension (PAH, 7 patients) or pulmonary hypertension and ILD (PH-ILD, 10 patients). The association of serum cytokines with clinical features was analysed and their correlation with BAL cytokines measured in a subset of SSc patients with ILD. Results: Serum cytokines were detected at different levels: high (TGF-β, median 287.5 pg/ml; CCL2, median 89.7 pg/ml; CCL4, median 104.2 pg/ml), low (IL-6, median 3.2 pg/ml; IL-7 median 2.3 pg/ml; IL-8, median 5.2 pg/ml; TNF-α, median 0 pg/ml but with a bimodal distribution) and very low (IL-10, median 0.4 pg/ml). IL-6 and IL-7 were predictive for death in a Cox regression analysis in all SSc patients as well as in all patients with pulmonary involvement; IL-6 was predictive for mortality in SSc-ILD patients. In a multivariate analysis, cytokine levels could also predict a change in lung function, e.g. IL-7 was a predictor for a decline of diffusion capacity (DLCO) by 20 or 30% in ILD patients. In a subset of ILD patients, serum cytokines were compared to BAL cytokines, but revealed only few correlations. Conclusion: In conclusion, the analysis of serum cytokines implicates a role as biomarkers, distinct from BAL.